The Brussels Effect 2.0: How the EU sets global standards with its trade policy - Elisabeth Christen; Birgit Meyer; Harald Oberhofer; Julian Hinz; Katrin Kamin; Joschka Wanner (FIW - Research Centre International Economics, 2022)
The creation of uniform, legally binding norms and standards is an essential basis for the functioning of the EU single market, which at the same time is increasingly spread beyond the EU's borders through international trade relations. The shaping of global standards and regulations according to EU directives even beyond the EU's borders represents an important competitive advantage of the EU. The EU also manages to impose rules, regulations and standards only through market mechanisms in third countries without international treaties or agreements. This has in many areas contributed to the "Europeanisation" of important aspects of global trade. In the academic literature, this regulatory influence of the EU is defined as the "Brussels Effect". The focus of this study is to give a comprehensive overview of the Brussels Effect and to analyse the linkages regarding EU trade policy, outlining to what extent a Brussels Effect can be observed in the network of EU trade agreements. Based on a comprehensive and broad identification of the Brussels Effect, this study aims to quantify the trade effects in terms of the leading role in shaping global standards and regulations for the EU and Austria and to qualitatively identify further areas in which untapped potentials of a "Brussels Effect 2.0" seem possible in the context of EU trade policy.
Keywords: 330